2010
DOI: 10.1007/s10995-010-0663-y
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Health: Awareness, Planning, and Communication Among a Sample of US Men and Women

Abstract: It is important to educate both men and women about preconception health (PCH), but limited research exists in this area. This paper examines men's and women's awareness of exposure to PCH information and of specific PCH behaviors, PCH planning, and PCH discussions with their partners. Data from Porter Novelli's 2007 Healthstyles survey were used. Women and men of reproductive age were included in the analysis (n = 2,736) to understand their awareness, planning, and conversations around PCH. Only 27.9% of wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 25 publications
1
72
1
Order By: Relevance
“…The lack of interest and practice of preconception care for men was consistent in our study and in line with other research (34); the majority of the GPs did not view men’s preconception health as a priority. Studies show that men have a lower knowledge of preconception care and are less likely to see their GP for preconception interventions (35). This is congruent with men’s limited involvement in reproductive and sexual health for preventive health care in general (36).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of interest and practice of preconception care for men was consistent in our study and in line with other research (34); the majority of the GPs did not view men’s preconception health as a priority. Studies show that men have a lower knowledge of preconception care and are less likely to see their GP for preconception interventions (35). This is congruent with men’s limited involvement in reproductive and sexual health for preventive health care in general (36).…”
Section: Discussionmentioning
confidence: 99%
“…There are significant challenges and barriers, however, that impede the dissemination of PCC: lack of awareness (38)(39)(40)(41)(42), not seeing oneself as at risk (40), ambivalence toward seeking PCC (42), and cultural norms that do not prioritize family planning (38,43). Professionals also report barriers in providing PCC: lack of awareness of guidelines to provide PCC (41,44) and lack of time (42,45).…”
Section: Effects Of Substance Use On Reproductive Healthmentioning
confidence: 99%
“…In fact, the definition of PCC is not inclusive of men (41,46). Consequently, men are less aware of PCC, less likely to discuss childbearing with their doctor, and less likely to discuss PCC with their partner (40). For example, Frey et al reported that, of the 39% men in their study who were interested in receiving PCC, only 8% recalled discussing PCC with their doctor (47).…”
Section: Effects Of Substance Use On Reproductive Healthmentioning
confidence: 99%
“…The most current estimate identified that among all women with recent live births about 30% reported pre-pregnancy health counseling receipt, and among women aged 35 and older 42% reported such care (D'Angelo et al, 2007). Although a recent national survey showed 11% of men aged 18-64 reported having seen, heard or read anything about recommendations for women's preconception health from their healthcare provider, this study did not examine the proportion of men in need of preconception care (Mitchell et al, 2012). Estimates for men in need of preconception care can provide a greater understanding of men needing preconception health services.…”
Section: Introductionmentioning
confidence: 97%